PERAN BANK THITIL DALAM KEHIDUPAN MASARAKAT EKONOMI LEMAH (STUDI KASUS PENYALURAN KREDIT OLEH BANK THITIL TERHADAP PEDAGANG SAYUR DI PASAR KESAMBEN KABUPATEN BLITAR) - Regar Elisa; Idah zuhroh (Jurnal Ilmu Ekonomi JIE, 2017)
The aim of this research to described thitilbank profile, to described a reason for the vegetable traders in Kesamben market of Blitar regency was using thitilbank to fulfilling their need and testing thitilbank that able to improved their standard living of vegetable traders in Kesamben market of Blitar regency.Method and analysis tool that’s used for this research is with the step of checking back the data obtained or collected from interview results from respondent, took into the data that was collected into a tabular form with a simple frequency distribution, recapitulate the data that was collected to tabular form, described the data which is obtained from recapitulation results and also using different test analysis tools paired sample t-test.From the result of this study shows that Thitilbank was the one channeling funds in the informal sector that’s provide money without assurance for vegetable traders in Kesamben markets of Blitar regency that’s underfunded. With the practice of offering loan money directly with coming to prospective customers. That’s what causes the vegetable traders in Kesamben market of Blitar regency prefer thitilbank in the fulfillment of money due to convenience and service thitilbank. From the result of analysis different tests paired sample t-test shows that there are different income of vegetable traders in Kesamben market of Blitar regency after comparison before receiving credit from thitilbank. This proved from vegetable traders in Kesamben market of Blitar regency before receiving credit from thitilbank on average of the income that was Rp.99.375 every day, then after receiving credit an average of the income beverage traders in Kesamben market of Blitar regency amount of Rp.112.250 every day.Keyword : Thitilbank, Vegetable seller, Standard of living.